2002
DOI: 10.1074/jbc.m201168200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mitochondrial Creatine Transport Activity

Abstract: Immunoblotting of isolated mitochondria from rat heart, liver, kidney, and brain with antibodies made against N-and C-terminal peptide sequences of the creatine transporter, together with in situ immunofluorescence staining and immunogold electron microscopy of adult rat myocardium, revealed two highly related polypeptides with molecular masses of ϳ70 and ϳ55 kDa in mitochondria. These polypeptides were localized by immunoblotting of inner and outer mitochondrial membrane fractions, as well as by immunogold la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Isolation of Purified Mitochondria and of Submitochondrial Fractions-Mitochondria from male Wistar rat liver were isolated by differential centrifugation and Percoll gradient according to Hovius et al (29) with some modifications (30). Importantly, swelling of the pure mitochondrial preparation was carried out in buffer containing 30% glycerol, which disrupts the mitochondrial contact sites between mitochondrial inner membrane and outer membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Purified Mitochondria and of Submitochondrial Fractions-Mitochondria from male Wistar rat liver were isolated by differential centrifugation and Percoll gradient according to Hovius et al (29) with some modifications (30). Importantly, swelling of the pure mitochondrial preparation was carried out in buffer containing 30% glycerol, which disrupts the mitochondrial contact sites between mitochondrial inner membrane and outer membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Both immunoflurescence and immunoelectron microscopy studies demonstrated two major creatine transporter protein species of ~55 and ~70kDa associated with the inner mitochondrial membrane, as would be expected for a mitochondrial transporter, both having a low affinity (high K m~1 5mM ) to creatine [3]. Western blot studies indicated that a creatine transporter having molecular mass ~58kDa is located in the plasma membrane and is responsible for high affinity (low K m ~ 20-50 μM - [59]) uptake of creatine [59].…”
Section: The Creatine Transportermentioning
confidence: 86%
“…These data suggest that creatine transporter is a system made up of two separate creatine transporters: the high affinity plasma membrane creatine transporter (PM-CRT) and the low affinity mitochondrial creatine transporter (Mi-CRT). They suggest a compartmentation of two intracellular creatine pools, in the cytosol and in mitochondria, respectively, in addition to a third pool, blood creatine [3].…”
Section: The Creatine Transportermentioning
confidence: 98%
See 2 more Smart Citations